(3JMbjb GdfUQg aj JdNjU eYGde OGQ GdgLQIs - (3CHh HcQ (B((3YHO Gddg(B) (3Hf GdMSjf Hf YeQ, CHh eMeO GdeUQj GdTGaYqj GdeQGZj GdbQTj, Rjf GdOjf,J (B816 (3g` s ((3eMeO Hf jYbhH Hf Ydi Hf OGhO Hf YHO Gddg Hf eMeO GdeGdci GdRHjQi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdeOjfI GdTQjah OGQ GdgLQI HQShdg s
(3BNQgG (B:s
(3aQZJ ef JHjVI jhe GdSHJ GdeHGQc (B12 (3QLH GdaQO SfI (B766(3g` s
(3GfXQ Qbe (B157 (3Qbe (B615 (3JGQjNs
(3fSNI NGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B63 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B60s
Keywords: (3GdJGQjNs